2022
DOI: 10.3390/ma15238422
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Calcium Carbide Method and Darr Drying to Quantify the Amount of Chemically Bound Water in Early Age Concrete

Abstract: Hydration is the exothermic reaction between anhydrous cement and water, which forms the solid cement matrix of concrete. Being able to evaluate the hydration is of high interest for the use of both conventional and more climate-friendly building materials. The experimental monitoring is based on temperature or moisture measurements. The first needs adiabatic conditions, which can only be achieved in laboratory. The latter is often measured comparing the weight of the material sample before and after oven dryi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Zajac et al [12] found, through research, that high temperatures can result in densification of the matrix, which limits further reaction progress. Strangfeld et al [13] studied the effect of high temperatures on the degree of concrete hydration and proposed a laboratory method for testing the degree of hydration. Farqad et al [14] analyzed the effect of high temperatures on the hydration rate of cement pastes.…”
Section: Introductionmentioning
confidence: 99%
“…Zajac et al [12] found, through research, that high temperatures can result in densification of the matrix, which limits further reaction progress. Strangfeld et al [13] studied the effect of high temperatures on the degree of concrete hydration and proposed a laboratory method for testing the degree of hydration. Farqad et al [14] analyzed the effect of high temperatures on the hydration rate of cement pastes.…”
Section: Introductionmentioning
confidence: 99%